UTILIZING BIOTECHNOLOGY TOOLS FOR SILECTING SALT TOLERANT ROOTSTOCK OF PEACH HASSAWI - & Alturki, Shehata (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was carried out with an aim of evaluation of performance of Hassawi peach rootstocks and testing their variance towards salinity stress thus to find out a quick effective modern technique for their reculture and re-propagation again in the region. Eight different concentrations of sodium chloride (NaCl) that represent progressive gradual levels of salinity were used to investigate tolerability of the explants towards variant levels of salinity stress. Thus to evaluate the performance of these Hassawi peach rootstocks (peach, plum ]ghwj[, and almond). Date and results declared the general superiority of bitter almond to the other rootstocks, as it vitally survived and tolerated salinity to 3500 ppm NaCl, followed by peach that tolerated salinity to 2500 ppm, and eventually ghwj that just survived with maximum tolerance of 2000 ppm of NaCl. The study recommends to count on bitter almond as a salinity tolerant rootstock followed by peach for grafting Hassawi peach rootstocks for its regeneration again in Al-Ahsa oasis, and to exclude plum rootstock because of its low salinity tolerance besides its very low harmonization with peach that negatively affect grafting process.